2016
DOI: 10.1160/th15-11-0848
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemia-associated Rho guanine nucleotide exchange factor (LARG) plays an agonist specific role in platelet function through RhoA activation

Abstract: Summary Leukemia-Associated RhoGEF (LARG) is highly expressed in platelets, which are essential for maintaining normal hemostasis. We studied the function of LARG in murine and human megakaryocytes and platelets with Larg knockout, shRNA-mediated knockdown and small molecule-mediated inhibition. We found that LARG is important for human, but not murine, megakaryocyte maturation. Larg KO mice exhibit macrothrombocytopenia, internal bleeding in the ovaries and prolonged bleeding times. KO platelets have impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The RhoA/RhoA kinase signaling pathway plays an important role the pathogenesis of PH, and inhibiting the RhoA/RhoA kinase pathway is a promising therapy for the treatment of PH [11,24]. Guanine exchange factors (GEF) are known to couple Gα subunits and Rho signaling, and there are multiple GEFs that can potentially function in platelet signal transduction from Gα subunits to RhoA [25]. Leukemia-associated RhoGEF (ARHGEF12) plays a critical role in the RhoA/RhoA kinase pathway [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RhoA/RhoA kinase signaling pathway plays an important role the pathogenesis of PH, and inhibiting the RhoA/RhoA kinase pathway is a promising therapy for the treatment of PH [11,24]. Guanine exchange factors (GEF) are known to couple Gα subunits and Rho signaling, and there are multiple GEFs that can potentially function in platelet signal transduction from Gα subunits to RhoA [25]. Leukemia-associated RhoGEF (ARHGEF12) plays a critical role in the RhoA/RhoA kinase pathway [25].…”
Section: Discussionmentioning
confidence: 99%
“…Guanine exchange factors (GEF) are known to couple Gα subunits and Rho signaling, and there are multiple GEFs that can potentially function in platelet signal transduction from Gα subunits to RhoA [25]. Leukemia-associated RhoGEF (ARHGEF12) plays a critical role in the RhoA/RhoA kinase pathway [25]. However, the role of ARHGEF12 in PH is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Gqmediated responses require much higher concentrations of U‐46619 (1). Considering that U‐46619‐activated TPαRs couple equally well with Gq and G 13 (41), together with the observation that LARG is involved in the Gα 13 mediated platelet response (42), it seems likely that the high agonist sensitivity of the Gα 13 response originates in its high‐affinity interaction with LARG.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ARHGEF12 may be responsible for RhoA activity in resting platelets only (67). In contrast, Zou et al (68) reported ARHGEF12 was necessary for RhoA activation in platelets. MLC phosphorylation by ROCK (downstream of RhoA-GTP) was abolished, albeit in a global ARHGEF12 knockout mouse model.…”
Section: Rhogefs In Plateletsmentioning
confidence: 91%